Microbial-Assisted Phytoremediation: A Convenient Use of Plant and Microbes to Clean Up Soils - Pinto, A. P. (2019)
Environmental pollution by metal(loid)s (e.g., heavy metals—HMs) is a severe problem worldwide, as soils and aquatic resources became increasingly contaminated, threatening land ecosystems, surface and groundwater, as well as food safety and human health. The primary sources contributing to this extended pollution are anthropogenic inputs related to the burning of fossil fuels, mining and continued industrial activities, disposal of municipal solid wastes and wastewater discharges or use for irrigation, and excessive utilization of fertilizers and pesticides. A consequence of these anthropogenic activities is an increase of contaminated areas, which should be remediated to prevent or mitigate transfer of contaminants into terrestrial, atmospheric, or aquatic environments. Point and diffuse contamination by organic and inorganic pollutants causes wide concerns, and intentional or accidental introduction of these substances in the environment may represent serious impacts on public health.